Response surface methodology for the optimization of Keratinase production in culture medium containing feathers by Bacillus sp. UPM-AAG1 - Abdul Gafar, Aa’ishah; Khayat, Mohd Ezuan; Ahmad, Siti Aqlima; Yasid, Nur Adeela (MDPI, 2020)
Keratinase is a type of proteolytic enzyme with broad application in industry. The main objective of this work is the optimization of keratinase production from Bacillus sp. strain UPM-AAG1 using Plackett-Burman (PB) and central composite design (CCD) for parameters, such as pH, temperature, feather concentration, and inoculum size. The optimum points for temperature, pH, and inoculum and feather concentrations were 31.66 °C, 6.87, 5.01 (w/v), and 4.53 (w/v), respectively, with an optimum keratinase activity of 60.55 U/mL. The keratinase activity was further numerically optimized for commercial application. The best numerical solution recommended a pH of 5.84, temperature of 25 °C, inoculums’ size of 5.0 (v/v), feather concentration of 4.97 (w/v). Optimization resulted an activity of 56.218 U/mL with the desirability value of 0.968. Amino acid analysis profile revealed the presence of essential and non-essential amino acids. These properties make Bacillus sp. UPM-AAG1 a potential bacterium to be used locally for the production of keratinase from feather waste.